Health Rights and Realization: Comment on "Rights Language in the Sustainable Development Agenda: Has Right to Health Discourse and Norms Shaped Health Goals?" - Rushton, Simon (Int J Health Policy Manag, 2016)
In their hypothesis published in IJHPM, Lisa Forman and colleagues examined the prominence of the right to health and sexual and reproductive health rights (as well as related language) in four of the key reports that fed into the process of negotiating the Sustainable Development Goals (SDGs). Now that the SDGs have been formally adopted, this comment builds on some of the insights of Forman and colleagues to examine the extent to which those rights have been incorporated in SDGs 3 and 5. I argue that sexual and reproductive health rights are relatively well-covered within the SDGs. In terms of the right to health, however, the picture is much less clear. Some of the elements that make up that right are present and correct, but the SDGs have delivered no coherent vision of how a ‘right to health’ might actually be realized. An important task facing global health and human rights advocates is to continue pushing human rights framings so that progress is made both on meeting the SDGs and on realizing the right to health.